Frontispiece: Establishing Radiolanthanum Chemistry for Targeted Nuclear Medicine Applications. Issue 6 (30th January 2020) - Aluicio‐Sarduy, Eduardo; Thiele, Nikki A.; Martin, Kirsten E.; Vaughn, Brett A.; Devaraj, Justin; Olson, Aeli P.; Barnhart, Todd E.; Wilson, Justin J.; Boros, Eszter; Engle, Jonathan W.
Abstract : The image describes the radiochemical complexation of the novel radionuclides 132 La and 135 La for coupling with prostate cancer targeting moieties, with efficacy quantified by in vivo positron emission tomography imaging in a mouse model. For more information, see the Communication by J. J. Wilson, E. Boros, J. W. Engle, et al. on page 1238 ff.